2021
DOI: 10.3389/falgy.2021.692049
|View full text |Cite
|
Sign up to set email alerts
|

Der p 1 Disrupts the Epithelial Barrier and Induces IL-6 Production in Patients With House Dust Mite Allergic Rhinitis

Abstract: Background:Dermatophagoides pteronyssinus 1/2 (Der p 1/Der p 2) are regarded as important allergens of house dust mite (HDM). However, the effect of both products on the epithelial barrier and immune response of patients with and without HDM allergic rhinitis (AR) remains unclear.Methods: Air–liquid interface (ALI) cultured human nasal epithelial cells (HNECs) derived from control subjects (non-AR) (n = 9) and HDM-AR patients (n = 9) were treated with Der P 1 and Der P 2, followed by testing the transepithelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…Data are the mean ± SD of three replicates per group as compared to the PBS group. ***P < 0.001. appearance of inflammatory symptoms, such as airway hyperresponsiveness and inflammation in lung tissue (66,67). These indicated that the results of in-vitro and in-vivo experiments are consistent.…”
supporting
confidence: 62%
See 1 more Smart Citation
“…Data are the mean ± SD of three replicates per group as compared to the PBS group. ***P < 0.001. appearance of inflammatory symptoms, such as airway hyperresponsiveness and inflammation in lung tissue (66,67). These indicated that the results of in-vitro and in-vivo experiments are consistent.…”
supporting
confidence: 62%
“…Generally speaking, in-vivo studies were needed to validate the finding of the in-vitro study. In previous studies, in-vitro experiments showed that Der f 20 and Der p1 from dust mites mainly function in promoting the release of pro-inflammatory cytokines of dendritic cells and epithelial cells, and the in-vivo experiments revealed similar functions of promoting the appearance of inflammatory symptoms, such as airway hyperresponsiveness and inflammation in lung tissue ( 66 , 67 ). These indicated that the results of in-vitro and in-vivo experiments are consistent.…”
Section: Discussionmentioning
confidence: 96%
“…Der p 1 and Der p 2 are the major components of Dp extracts and are regarded as the most important allergens. Der p 1, a 25 kDa protein that mainly exists in the excrement of mites [15], induces allergic responses by reducing the effectiveness of the epithelial barrier [16]. It has enzymatic activity as a cysteine protease, and epithelial cells may be its primary proteolytic target.…”
Section: Discussionmentioning
confidence: 99%
“…Majorly, HDM allergens trigger allergic asthma in sensitized individuals with elevated specific-IgE titer. According to clinical reports, the cysteine proteases and lipid-binding proteins are the primary allergens in HDM, which belong to groups 1 and 2 allergens, respectively (18).…”
Section: Discussionmentioning
confidence: 99%